Key Concepts and Models of Strategic Innovation Management in Ukraine: Modern Approaches - Skrypnyk Svitlana V. (Problemi Ekonomiki)
The current stage of economic development is characterized by unprecedented rates of technological change, market globalization, and increasing competitive pressure, which poses new complex challenges for enterprises in the field of innovation management. This article is dedicated to a comprehensive analysis of modern conceptions and models of strategic innovation management through the lens of transformational changes occurring in both the Ukrainian and global economies. The research is particularly relevant due to the necessity of adapting traditional approaches to the conditions of the digital economy, global crises (such as the COVID-19 pandemic and the ongoing war in Ukraine), and growing demands for sustainable development. The analysis is based on a systemic study of scientific works by leading Ukrainian researchers, which has allowed for the identification and classification of three key directions in the development of the theory of strategic innovation management. The first direction is associated with adaptive management models, which gain particular significance in conditions of instability and uncertainty. The second direction encompasses the digital transformation of innovation processes, particularly the implementation of artificial intelligence, big data technologies, and the Internet of Things. The third direction emphasizes the integration of ESG (environmental, social, and governance) principles into the innovation strategies of enterprises. An important aspect of the research is the analysis of the specifics of the Ukrainian context, particularly the impact of the war on innovation processes and the need to develop special crisis management models. The research results demonstrate that traditional linear models of innovation management are losing their efficiency and are being replaced by more flexible approaches such as Agile, Lean Startup, and other iterative methods. Special attention is given to analyzing the obstacles to the implementation of innovative strategies in Ukrainian conditions, including insufficient funding, weak integration of science and business, and limited access to international technology markets. The article provides a detailed systematization of contemporary models of strategic management of innovations, considering their strengths and weaknesses, as well as the areas of most effective application. The suggestions for developing hybrid models that combine elements of ecosystem approaches, open innovations, and digital solutions are particularly valuable in practice. The model of strategic financing of innovations proposed by the author is aimed at stimulating innovative activity and ensuring sustainable economic growth. The research also highlights promising directions for further development of the theory of strategic management of innovations in Ukraine, particularly the need for a comprehensive methodology that would consider the specifics of the domestic economy and individual sectors.